1994
DOI: 10.1007/bf01229076
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-fetoprotein-producing early gastric cancer accompanying liver cirrhosis: A case report

Abstract: A rare case of alpha-fetoprotein (AFP)-producing early gastric cancer with liver cirrhosis is presented. A 61-year-old man was admitted to Shimane Medical University Hospital in 1988 because of abnormal liver function test results suggestive of liver cirrhosis with mild elevation of AFP. Liver cirrhosis was confirmed laparoscopically and histologically. Gastric cancer was found in fluoroscopic and endoscopic studies. After partial gastrectomy, the serum AFP level fluctuated transiently within normal limits, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Later, some researchers define "AFPGC" as "immunohistochemical AFP positivity of tissues." In 1981, Kodama et al verified the expression of AFP in gastric cancer, through immunohistochemistry, and established the concept of "AFP-producing gastric cancer" [24] and some other researchers defined "AFPGC" as "positive of AFP in both serum and tissue" [17]. Histological types of AFPGC can be classified as gastric hepatoid, enteroblastic, papillotubular adenocarcinoma, and yolk sac tumors [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, some researchers define "AFPGC" as "immunohistochemical AFP positivity of tissues." In 1981, Kodama et al verified the expression of AFP in gastric cancer, through immunohistochemistry, and established the concept of "AFP-producing gastric cancer" [24] and some other researchers defined "AFPGC" as "positive of AFP in both serum and tissue" [17]. Histological types of AFPGC can be classified as gastric hepatoid, enteroblastic, papillotubular adenocarcinoma, and yolk sac tumors [13].…”
Section: Discussionmentioning
confidence: 99%
“…As a diagnostic rule, serum AFP levels of most AFPGC were only slightly higher than normal, but in some cases, they were as high as several thousand ng/mL or more, even beyond the detection limit [15][16][17]. Some researchers observed that certain lesions mimicked HCC-like morphology under the light microscope, especially in these AFPGCs with high serum level of AFP.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows the 24 cases of AFPEGC reported in Japan in the past 15 years, including the present case (1)(2)(3)(4)(5)(6)(7)(8). The male to female ratio was 17 : 7, the mean age was 64.4 years (range, 41 to 79 years), and the primary symptom at the time of onset was epigastralgia (29.2%).…”
Section: Discussionmentioning
confidence: 99%
“…In AFPGC patients, liver metastases are often noted (2) and the tumor often has progressed to advanced gastric carcinoma at the time of diagnosis. In Japan, AFP-producing early gastric carcinoma (AFPEGC) is extremely rare and only 23 cases have been reported in the past 15 years (1)(2)(3)(4)(5)(6)(7)(8). Herein we report the case of a man diagnosed with seronegative AFPEGC treated with endoscopic mucosal resection (EMR) and additional surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Many other reports followed [2, 3, 4, 5]. These studies showed that AFP-producing gastric cancer is characterized by the frequent occurrence of liver metastases [5, 6, 7, 8, 9], and that even with early diagnosis the prognosis is poor [8, 9, 10, 11]. Up to now, there is still much controversy regarding the treatment of AFP-producing gastric cancer.…”
Section: Introductionmentioning
confidence: 99%